Le Fabuleux Destin d’Amélie Poulain: A Psychological Case Study in the uses of enchantment (Existential Analysis: Journal of the Society for Existential Analysis, 2022)
The highly-acclaimed 2001 French film Le Fabuleux Destin d'Amélie Poulain has been described by critics as, variously, the quintessential 'feel-good' movie, a late example of 'Cinema du Look' and quirky romantic comedy. While each of these descriptions capture an aspect of the film, they do not succeed in explaining its enduring appeal or its disconcertingly unsettling engagement with the casual cruelty of life. I will suggest that an analysis of the way in which director Jean-Pierre Jeunet draws on elements of both classical and art cinema may lead us to a third reading, one that references the fairy story tradition. I will argue, drawing on the work of Bruno Bettelheim, that Amélie can be understood as a psychological case study in the uses of enchantment, in the course of which Amélie, the eponymous heroine and thaumatürge, constructs an ingenious but increasingly dysfunctional response to trauma and the absurd.
Keywords: Amélie; film; existential case study; Bruno Bettelheim; enchantment